Conceptualisations of wellbeing and quality of life: A systematic review of participatory studies. (December 2022) - Sollis, Kate; Yap, Mandy; Campbell, Paul; Biddle, Nicholas
Highlights: Participatory wellbeing studies have been undertaken in varied contexts throughout the world. Researchers and practitioners can draw on the methodologies of studies in this review to enhance their own projects. Most studies in the review used more standard research methods, with few utilising higher levels of participation. While there are similarities in what wellbeing means to different population groups, nuances exist within every community. To ensure meaningful impact, policymakers should consider how the population groups they work with understand wellbeing. Abstract: There is a growing movement across the world to make better use of wellbeing measures to guide policy. This stems from the realisation that reliance on economic indicators, such as income, GDP, and unemployment, may not be adequately capturing the aspects of life that people value. But how should we be measuring wellbeing or quality of life? A mounting body of research over the past two decades has highlighted the value of participatory wellbeing frameworks, which are created by working with the population of interest and asking the question "What does wellbeing mean for you?". However, up to now there is very little consolidated understanding of the work conducted in this space. This systematic review seeks to fill this gap, identifying 130 participatory wellbeing studies which span every region of the world and all life stages. The review identifies a wide range of theories, methods, and participatory techniques that have been utilised to develop participatory wellbeing frameworks which can be replicated for similar studies going forward. By thematically analysing understandings of wellbeing into 30 overarching areas, the findings show that communities and population groups throughout the world have wide-ranging and diverse conceptualisations of wellbeing. In sum, we highlight that while there are some similarities in what wellbeing means to people from different population groups, nuances exist within every group. Given this diverse understanding of wellbeing throughout the world, it is vital that research, policy and development initiatives take this into account. Doing so will help support policy and programs to address the aspects of life that are important to individuals, and subsequently improve the lives of people throughout the world in a more meaningful way.